Synovial sarcoma of the floor of the mouth: a rare case report - Yannan Wang; Feiya Zhu; Kai Wang (BMC, 2020)
Abstract Background Head and neck Synovial sarcoma (SS) accounts for 3-10% of all total body SS. It is rare to find it in the oral cavity, especially on the floor of the mouth. Case presentation We present a 44-year-old Chinese male, who had been misdiagnosed as fibroadenoma, with a swelling on the right submandibular region for more than 3 months. The radiology examinations and the pathology results indicate the diagnosis of SS of the floor of the mouth. The patient only had a surgical operation, without radiotherapy and chemotherapy. At the first follow-up, the patient exhibited no clinical or radiographic complications, and the patient was asymptomatic on subsequent visits. Conclusions Misdiagnosis results the delay of diagnosis and treatment of SS. Immunohistological analysis might be the most important tool to confirm the diagnosis of SS.